Inhibitory Action of 5-HT1A Agonist MKC-242 on Triazolam-Induced Phase Advances in Hamster Circadian Activity Rhythms - Shin-ichi Yokota; Takahiro Moriya; Shigenobu Shibata (Elsevier, 2005)
Mammalian circadian rhythms can be entrained by photic and non-photic stimuli. Although we know that non-photic entrainment interferes with photic entrainment signals, there is no information about whether photic entrainment interferes with non-photic entraining signals. We examined whether triazolam (TRZ), a non-photic form of entrainment, could be attenuated by pre-treatment with (S)-5-[3-[(1,4-benzodioxan-2-ylmethyl)amino]propoxy]-1,3-benzodioxole hydrochloride (MKC-242), a photic enhancing drug. We found that TRZ-induced phase advances in hamster behavioral circadian rhythms and the increase of locomotor activity were both significantly attenuated by MKC-242. Thus, in hamsters, the photic enhancing drug MKC-242 seemed to hinder benzodiazepine-induced non-photic entrainment. Keywords:: circadian rhythm, non-photic, benzodiazepine